Vários modos de se dizer o nada : as figuras niilistas de Kierkegaard entre a filosofia e a literatura - Jean dos Santos Vargas (2021)
The present investigation aims to think about the theme of nihilism from the reflections of Søren Kierkegaard. The great philosophical problem of nihilism remained until then a theme, if not unprecedented, at least quite dilettante, judging by the fact that nihilism as a philosophical concept is consolidated after Kierkegaard. Considering Kierkegaard's reflections about Hegelian philosophy and romantic literature, the main claims of this research are: Kierkegaard deals with the phenomenon of nihilism in its context, even before the concept, by engaging in the quarrel between Hegel and the German Romantics; Kierkegaard sometimes takes back the romantics, sometimes Hegel to build his own path; the Nordic philosopher makes use of nihilistic figures, such as irony and boredom, to think of the malaise evidenced by modern nothingness.